Improving the cancer prevention/treatment role of carotenoids through various nano-delivery systems. Issue 3 (4th February 2021) - Zare, Mahboobeh; Norouzi Roshan, Zahra; Assadpour, Elham; Jafari, Seid Mahdi
Abstract: One of the emerging and recent strategies to combat cancer is application of natural bioactive compounds and phytochemicals. Carotenoids including lycopene, β -carotene, astaxanthin, crocin, β -cryptoxanthin, and lutein, are the main group of plant pigments which play important roles in the prevention and healing process of different diseases including cancer. The pharmacological use of carotenoid compounds is frequently limited by their low bioavailability and solubility as they are mainly lipophilic compounds. The present study focuses on the current data on formulation of different carotenoid nanodelivery systems for cancer therapy and a brief overview of the obtained results. Encapsulation of carotenoids within different nanocarriers is a remarkable approach and innovative strategy for the improvement of health-promoting features and particularly, cancer prevention/treatment roles of these compounds through enhancing their solubility, cellular uptake, membrane permeation, bioaccessibility, and stability. There is various nanocarrier for loading carotenoids including polymeric/biopolymeric, lipid-based, inorganic, and hybrid nanocarriers. Almost in all relevant studies, these nano delivery systems have shown promising results in improving the efficiency of carotenoids in cancer therapy.